Identiï¬cation and characterisation of DfCHS, a chalcone synthase gene regulated by temperature and ultraviolet in Dryopteris fragrans - Sun, L. L.; Li, Y.; Li, S. S.; Wu, X. J.; Hu, B. Z.; Chang, Y. (Cellular and Molecular Biology, 2014)
Chalcone synthase (CHS) is an enzyme that catalyzes the first committed step in flavonoid biosynthesis, and its transcription level is regulated by light conditions. By using homology cloning and rapid amplification of cDNA ends, we cloned a chalcone synthase gene (DfCHS) from Dryopteris fragrans (L.) Schott. The full-length cDNA of DfCHS is 1,737 bp, with an open reading frame (ORF) of 1,122 bp (deposited in GenBank under Accession Number KF530802) encoding a predicted protein of 373 amino acids. The calculated molecular mass of DfCHS is 41.3 kDa. We studied the expression of DfCHS and total flavonoid contents in tissue culture seedlings cultured under the low temperature at 4ºC, high temperature at 35ºC and UV conditions, respectively. The results show that the expression of DfCHS are not the same, but all present rising trends, then flavonoid contents were increased. Overall, our results imply that the expression of DfCHS gene provide a certain theory basis in the status of evolution among ferns.